1992
DOI: 10.1103/physrevb.46.1649
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the (001)- and (111)-oriented surfaces of the ordered fccPt3Sn alloy by low-energy-electron-diffraction intensity analysis

Abstract: The surface structure and composition of the (001)and (111)-oriented surfaces of the ordered Pt3Sn alloy were determined by low-energy-electron-difraction intensity analysis. For both orientations the surface structure corresponds to a bulk truncation model. For the (001) surface, the mixed "PtSn" plane forms the outermost surface layer. Sn atoms in the outermost plane are also significantly upwardly displaced (by about 0.2 A) for both the (001) and the (111)surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…38 Bardi and co-workers have measured the outward buckling of Sn on the surface of Pt 3 Sn(111) to be 0.21Ϯ0.08 Å with reference to the plane passing through the platinum atoms, 38 and we have calculated this value to be 0.19 Å. In general, the platinum atoms bonded to the adsorbate move upward upon adsorption, while the rest of the platinum or tin atoms move downward toward the metal slab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Bardi and co-workers have measured the outward buckling of Sn on the surface of Pt 3 Sn(111) to be 0.21Ϯ0.08 Å with reference to the plane passing through the platinum atoms, 38 and we have calculated this value to be 0.19 Å. In general, the platinum atoms bonded to the adsorbate move upward upon adsorption, while the rest of the platinum or tin atoms move downward toward the metal slab.…”
Section: Resultsmentioning
confidence: 99%
“…37 The calculated equilibrium lattice constant for the Pt 3 Sn bulk alloy is 4.08 Å, while the experimental value is 4.00 Å. 38 We have used a 2ϫ2 unit cell to study the adsorption of various species, corresponding to 1 4 monolayer coverage. Adsorption occurs on one side of the slab.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the early studies by qualitative LEED a c(2x2) bulk termination structure was observed, but also a a "streaked" LEED pattern was reported [20,30,32]. The structure of the c(2x2) phase was found by quantitative LEED to correspond to a simple bulk termination model, as expected [17]. The later STM studies [27] showed that the streaked pattern originates from mesoscopic features, "pyramids" on a relatively flat surface.…”
Section: Pt¢ Sn(001)mentioning
confidence: 68%
“…The atomic structure of this surface was studied by Atrei et. al [17] by quantitative LEED and found to correspond indeed to a simple bulk termination model. The other possible termination, the (A ¦ ¥ B A ¦ D R30E , was reported and studied in detail by Atrei et al [33] who also determined the atomic structure by means of quantitative LEED and found it to correspond to a single layer surface alloy.…”
Section: Pt¢ Sn(111)mentioning
confidence: 71%
See 1 more Smart Citation